Impact of climate change on the potential distributions of two cicada species, Platypleura octoguttata and Lemuriana apicalis (Hemiptera: Cicadidae), in India and their conservation implications - Babu SADDAM; Cong WEI (European Journal of Entomology)
The loss of habitat for numerous organisms due to climate change has significantly accelerated the rate of species extinction. Unfortunately, there have been no studies conducted on the impact of climate change and other factors on the distribution patterns of cicada species in India. In the present study, we investigated the current and potential future distribution of two cicada species, Platypleura octoguttata and Lemuriana apicalis, using environmental variables and occurrence data through maximum entropy modelling. The distribution ranges of both species show some similarities under the current climatic conditions. According to predictions based on future climate scenarios, the distribution areas for P. octoguttata and L. apicalis are predicted to decrease to varying extents. However, the anticipated reduction of distribution areas for these two cicada species is different, indicating that both species have distinct responses to climate change. The changes in the distributional centroids show a consistent trend of moving in a north-westward direction across all future periods under the four climate scenarios (SSP126, SSP264, SSP370, and SSP585), except for SSP370 in the case of L. apicalis, which shows the direction of overall migration north-eastwards over time. The creation of a new protected area at the border of Bijnor District in Uttar Pradesh Province and Haridwar District in Uttarakhand Province would be greatly helpful in future for the conservation of these two species. Our findings highlight the impact of climate change on the distribution range of these two cicada species, offering valuable insights for conservation efforts in India.